2011
DOI: 10.1021/mp1004614
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Primary Human and Animal Cell-Based Blood−Brain Barrier Models as a Screening Tool in Drug Discovery

Abstract: Brain penetration is characterized by its extent and rate and is influenced by drug physicochemical properties, plasma exposure, plasma and brain protein binding and BBB permeability. This raises questions related to physiology, interspecies differences and in vitro/in vivo extrapolation. We herein discuss the use of in vitro human and animal BBB model as a tool to improve CNS compound selection. These cell-based BBB models are characterized by low paracellular permeation, well-developed tight junctions and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 36 publications
3
54
0
1
Order By: Relevance
“…In some cases, transport parameters were first verified in isolated microvessels (closest to the in vivo situation), and then studied in cell culture systems 76,61 . Molecular biology research has allowed the characterization of gene and protein expression in isolated microvessels and low passage endothelial cell cultures from the same species, and between different species, most often from small animals such as rodents (mice and rats) or from cow and pig in comparison to humans 77,78,75,15 . Transcriptomic comparison between in vivo and in vitro brain microvascular endothelial cells showed numerous gene transcripts that were differentially expressed and most often significantly downregulated in vitro.…”
Section: Molecular and Functional Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, transport parameters were first verified in isolated microvessels (closest to the in vivo situation), and then studied in cell culture systems 76,61 . Molecular biology research has allowed the characterization of gene and protein expression in isolated microvessels and low passage endothelial cell cultures from the same species, and between different species, most often from small animals such as rodents (mice and rats) or from cow and pig in comparison to humans 77,78,75,15 . Transcriptomic comparison between in vivo and in vitro brain microvascular endothelial cells showed numerous gene transcripts that were differentially expressed and most often significantly downregulated in vitro.…”
Section: Molecular and Functional Characterizationmentioning
confidence: 99%
“…Transcriptomic studies also revealed important differences between species that further complicate predictions on drug uptake in humans based on rodent in vitro BBB models 75 . In vitro BBB models involving co-culture of human endothelial cells and astrocytes have been described 15 . Although relevant, these models are more difficult to implement on a regular basis as they require regulated access to post-mortem human tissue and there is heterogeneity in the quality/properties of the human brain endothelial cells depending on the age, diseases, and possibly medical treatment of donors.…”
Section: Molecular and Functional Characterizationmentioning
confidence: 99%
“…Although one human study suggested an association between peripheral and central BDNF concentrations [121], the evidence in humans is limited. Since the human BBB is structurally and functionally different from those in animal models, we cannot infer from those models that BDNF can cross the human BBB [128,129]. The roles of BDNF in the periphery are not well characterized and may involve regulation of energy homeostasis, modification of insulin activity, and modification of neuronal function in certain neuronal subpopulations in the peripheral nervous system [130][131][132].…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the current transwell model utilising transfected cell lines are its static nature and lack of availability of human cells. However, this system could be improved by using rat ECs and glial cells, to better represent the in vivo environment than is currently available with transfected cell lines alone, in order to account for the difference in permeability [62]. Due to the nature of individual transporter testing in current 2D cultures, 3D models exhibiting BBB characteristics could also be utilised for drug-drug interaction studies as the 3D liver models are starting to investigate.…”
Section: Neuhaus Et Almentioning
confidence: 99%